2017
DOI: 10.1016/j.physbeh.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral endocannabinoid signaling controls hyperphagia in western diet-induced obesity

Abstract: The endocannabinoid system in the brain and periphery plays a major role in controlling food intake and energy balance. We reported that tasting dietary fats was met with increased levels of the endocannabinoids, 2-arachidonoyl-sn-glycerol (2-AG) and anandamide, in the rat upper small intestine, and pharmacological inhibition of this local signaling event dose-dependently blocked sham feeding of fats. We now investigated the contribution of peripheral endocannabinoid signaling in hyperphagia associated with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 53 publications
(67 reference statements)
7
103
3
3
Order By: Relevance
“…Second, elimination the H-bond acceptor moiety caused a similar reduction of binding affinity between the wild-type receptor K3.28 and the mutant ligand VCHSR (Andre & Gonthier, 2010) to 31.3±9.6n M supporting the strong H-bonding interaction. Third, when both H-bonding donor and acceptor moieties were lacking, such as in the K3.28A–VCHSR pair (Argueta & DiPatrizio, 2017), the binding affinity was similarly reduced to 35.2±1.4n M , indicating the absence of an additive effect of both mutations supporting that they participate in the same H-bond interaction (Hurst et al, 2002). …”
Section: Computational Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, elimination the H-bond acceptor moiety caused a similar reduction of binding affinity between the wild-type receptor K3.28 and the mutant ligand VCHSR (Andre & Gonthier, 2010) to 31.3±9.6n M supporting the strong H-bonding interaction. Third, when both H-bonding donor and acceptor moieties were lacking, such as in the K3.28A–VCHSR pair (Argueta & DiPatrizio, 2017), the binding affinity was similarly reduced to 35.2±1.4n M , indicating the absence of an additive effect of both mutations supporting that they participate in the same H-bond interaction (Hurst et al, 2002). …”
Section: Computational Modelingmentioning
confidence: 99%
“…Other classes of CB1R regulators in the form of neutral antagonists, that do not change basal CB1R activity, have been revealed (Pan et al, 1998) and are the subject of study (Hurst et al, 2002, 2006; Pertwee, 2005a; Reggio, 2009; Silvestri & Di Marzo, 2012) and development (Alonso et al, 2012; Argueta & DiPatrizio, 2017; Bostroem et al, 2010; Brents et al, 2012; Franks et al, 2014; Fride et al, 2007; Greig & Ross, 2010; Kangas et al, 2013; Makriyannis & Vemuri, 2008; Ruiu et al, 2003; Vela Hernandez & Yenes Minguez, 2009; Wargent et al, 2013; Wiley et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…; Cluny et al . ; Argueta & DiPatrizio, ,) which is dependent on intact vagal afferent neurones (Capasso & Izzo, ; Izzo et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Endocannabinoids, however, are generated throughout the body, and cannabinoid receptors are present on extraneuronal cells, including intestinal epithelial cells and immune cells (12)(13)(14). Signaling by the endocannabinoids, 2-arachidonoylglycerol (2-AG) and anandamide (AEA), through cannabinoid receptors on intestinal cells impacts feeding behavior (15,16), while signaling on immune cells can promote anti-inflammatory pathways (17). Despite functional effects on intestinal physiology and immune responses, no studies reported to date have investigated the role of endocannabinoids in parasite infection.…”
mentioning
confidence: 99%